A territorial analysis of infrastructures in Italy - Skonieczny Giorgio; Torrisi Benedetto (European Regional Science Association (ERSA), 2002)
At a regional level the study of the infrastructures becomes really complicate when we consider: the territory equipment and the different potentiality of its development. Usually to this articulation corresponds even an analogue no homogeneity of the socio-economical conditions characterizing the various territorial areas. It is one of the most interesting aspect of the research to establish if and in which way these elements are connected among themselves, if it is possible that in an area the level of infrastructures can contribute to determine the development of the area or vice versa. To obtain this goal we must determine the quantity and quality of the infrastructures. In the reality the research of synthetic index and of the source of information - about the characteristics of the infrastructures - becomes an interesting instrument of the development polices. Even in the diversity of approaches, all the literature regarding the development and the competitiveness of modern productive systems agrees with the growing importance of the quantity and quality of the infrastructures. When we live the theoretical level to effectuate a check of the quantity and quality of the infrastructures in the reality the difficulties encountered aren't of easy solution nor few: findable ness of basic data, control of the minimum requisites of homogeneity and comparability, individuation of correct modality of statistic treatment, indicators building and so on. This research analyses the territorial diffusion of the infrastructures in the Italian regions. This is obtained through the application of qualitative and quantitative statistic indicators. Through the whole aggregation of data we try to determine a general indicator that measures the total level of the infrastructures.
Keywords: 330